Equity market anomalies: concepts, classifications, theories and evidence - Qaiser Munir; Kok, Sook ching (2016)
At the outset, it is important to understand the meaning of ‘anomalies’. In general, anomalies are known as irregularities or deviations from the natural order (George and Elton, 2001). Anomalies that arise from the trading of financial instruments are referred to as the moments when security prices depart from their normal behaviour (Dana and Cristina, 2013). In relation to stock trading specifically, Hubbard (2008) defines anomalies as the trading opportunities derived from the investment strategies that allow for earning above-normal returns.